2011
DOI: 10.5301/jn.5000034
|View full text |Cite
|
Sign up to set email alerts
|

Abated microRNA-195 expression protected mesangial cells from apoptosis in early diabetic renal injury in mice

Abstract: These results demonstrated that the abated microRNA-195 expression protected mesangial cells from apoptosis, suggesting that the antiapoptosis in a microRNA-regulated manner may play an important role in the early stages of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…These findings suggested that miR-195 might mediate podocyte apoptosis in DN. In line with this study, miR-195 was observed to be increased not only in STZ-induced type 1 diabetic mice but also in high glucose cultured MMCs, followed by enhanced apoptosis of MMCs [43]. …”
Section: Upregulated Mirnas In Dnsupporting
confidence: 73%
“…These findings suggested that miR-195 might mediate podocyte apoptosis in DN. In line with this study, miR-195 was observed to be increased not only in STZ-induced type 1 diabetic mice but also in high glucose cultured MMCs, followed by enhanced apoptosis of MMCs [43]. …”
Section: Upregulated Mirnas In Dnsupporting
confidence: 73%
“…A recent study showed a reduction in miR-195 in the kidney of STZ-induced type 1 diabetic mice [31]. However, upregulation of miR-195 was revealed in liver in a rat model of spontaneous type 2 diabetes [32] and in retinas of STZ-induced diabetic rats [33].…”
Section: Discussionmentioning
confidence: 99%
“…miR-195, a member of the miRNA family that play a role in DN etiology and physiology, show antiapoptotic features due to its down-regulation. Chen et al's [41] rat model study showed that in early stages of DN, miR-195 expression decreased, was along with a reverse association between miR-195 expression level and glomerular diameter. Higher than control urinary and plasma miR-195 expression levels in stage 3 and stage 5 CKD patients, respectively in the present study can be explained by the furthering of the renal parenchymal damage and primarily renal cortex damage in relation with miR-195 down-regulation; shrinking in the glomeruli; fibrosis; and increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%